Cystic fibrosis pathogens survive for extended periods within cough-generated droplet nuclei. Issue 1 (7th April 2018) - Wood, Michelle E; Stockwell, Rebecca E; Johnson, Graham R; Ramsay, Kay A; Sherrard, Laura J; Kidd, Timothy J; Cheney, Joyce; Ballard, Emma L; O'Rourke, Peter; Jabbour, Nassib; Wainwright, Claire E; Knibbs, Luke D; et al.
Abstract : The airborne route is a potential pathway in the person-to-person transmission of bacterial strains among cystic fibrosis (CF) populations. In this cross-sectional study, we investigate the physical properties and survival of common non- Pseudomonas aeruginosa CF pathogens generated during coughing. We conclude that Gram-negative bacteria and Staphylococcus aureus are aerosolised during coughing, can travel up to 4 m and remain viable within droplet nuclei for up to 45 min. These results suggest that airborne person-to-person transmission is plausible for the CF pathogens we measured.